Exploring metastable phase formation: Swift heavy ion effects on partially stabilized zirconia; Journal of Nuclear Materials; Vol. 602 - Kirilkin N. S. Nikita Sergeevich; Vershinina T. N.; O'Connell J. H. Jacques Herman; Rymzhanov R. A. Ruslan Alikovich; Skuratov V. A. Vladimir Alekseevich; Boltueva V. A. Valeria Alexandrovna; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (2024, 2024)
Zirconium dioxide shows great potential for use in the nuclear power industry. It exhibits high radiation stability (neutron and heavy ions) and can withstand harsh environments. The paper presents a study on the effects of 710 MeV Bi ion irradiation on polycrystalline partially yttria-stabilized zirconia using the combination of experimental techniques - X-ray diffraction, transmission electron microscopy and Raman spectroscopy. It was revealed that bismuth ion induced tracks retain their crystalline structure and their density tends to saturate at ∼1 × 1012 cm−2. As a result of dense ionization stimulated structural modification a t → t'' phase transformation was observed. The radiation stability of t'' phase against swift heavy ion impact was found to be higher compared to the t phase. No amorphization was detected up to Bi ion fluence of 2 × 1013 cm−2